Retention of Vanilla planifolia Jacks ex Andrews fruits with growth regulators - Hernández-Hernández, Juan; Curt-Díaz, Sergio Alberto; Ríos-Utrera, Ángel (Agronomía Mesoamericana, 2019)
Introduction. The vanilla production in Mexico has decreased by 70 % in the last fifteen years, due to the fall of its fruits. This occurs in extreme climatic conditions when the temperature is higher than 32 °C and the relative humidity is less than 80 %. Objective. The objective was to determine the effect of some commercial growth regulators (GR) on the retention of vanilla (Vanilla planifolia Jacks ex Andrews) fruits Mansa cultivar. Materials and methods. The study was carried out in 2016 in the Tecolutla Municipality, Veracruz, Mexico. The treatments evaluated were: aminoethoxyvinylglycine hydrochloride (AVG; 250 ppm), 1-naphthaleneacetic acid (ANA; 27 ppm), benzyl-adenine (BA; 150 ppm), forchlorfenuron (CPPU; 5 ml l-1 of water), 2,4-Dichlorophenoxyacetic acid (2,4-D; 32 ppm), 2,4-D (32 ppm) + CPPU (5 ml l-1 of water) and control, which consisted of applying only one acidifier (8 ml in 10 l of water). Treatments were applied three times to the same fruits, at 6, 20 and 31 days after the last flowers pollinated by bunch. Results. All GR retained more labelled fruits than the control. Treatments 2,4-D and 2,4-D + CPPU retained more fruits per raceme and produced significantly longer fruits than the control. In addition, the 2,4-D + CPPU mixture produced fruits with larger diameter than the control. The growth regulators AVG, ANA BA and CPPU did not differ in the number of labelled fruits, fruits per raceme, fruit length, and fruit diameter. Conclusion. GR had a positive effect on vanilla fruit retention, mainly the 2,4-D + CPPU mixture with which more labelled fruits and per bunch were obtained compared to the control. The use of GR was effective in reducing vanilla abortion.